Recent advances in the pathophysiology of PIEZO1‐related hereditary xerocytosis. Issue 8 (3rd May 2021) - Jankovsky, Nicolas; Caulier, Alexis; Demagny, Julien; Guitton, Corinne; Djordjevic, Stefan; Lebon, Delphine; Ouled‐Haddou, Hakim; Picard, Véronique; Garçon, Loïc
Abstract: Hereditary xerocytosis is a rare red blood cell disease related to gain‐of‐function mutations in the FAM38A gene, encoding PIEZO1, in 90% of cases; PIEZO1 is a broadly expressed mechano‐transducer that plays a major role in many cell systems and tissues that respond to mechanical stress. In erythrocytes, PIEZO1 adapts the intracellular ionic content and cell hydration status to the mechanical constraints induced by the environment. Until recently, the pathophysiology of hereditary xerocytosis was mainly believed to be based on the "PIEZO1‐Gardos channel axis" in erythrocytes, according to which PIEZO1‐activating mutations induce a calcium influx that secondarily activates the Gardos channel, leading to potassium and water efflux and subsequently to red blood cell dehydration. However, recent studies have demonstrated additional roles for PIEZO1 during early erythropoiesis and reticulocyte maturation, as well as roles in other tissues and cells such as lymphatic vessels, hepatocytes, macrophages and platelets that may affect the pathophysiology of the disease. These findings, presented and discussed in this review, broaden our understanding of hereditary xerocytosis beyond that of primarily being a red blood cell disease and identify potential therapeutic targets.